Phenotypic and Molecular Characterization of Vibrio Species Isolated from Fish markets in Egypt - GOBARAH, D.E.A.; HELMY, S.M.; MAHFOUZ, N.B.; FAHMY, H.A.; ABOU ZEID, M.A.M.; MOUSTAFA, E.M. (Journal of the Hellenic Veterinary Medical Society, 2021)
Vibriosis is considered a worldwide, threatening bacterial disease that affects mariculture, with high mortalities and severe economic losses. Some Vibrio species have been frequently involved in outbreaks of foodborne diseases worldwide. The Genus Vibrio includes over eighty-five species present in marine and natural habitats of seawater, and the species are widely distributed throughout the world. This work aimed to isolate Vibrio species from different markets in Kafr EL-Sheikh Governorate, representing 40% of Egypt’s fish production. Samples of Nile tilapia, (Oreochromis niloticus), grey mullet (Mugil cephalus) and African sharptooth catfish (Clarias gariepinus) were collected alive and examined for Vibrio species. Isolation and identification of Vibrio species were made using colonial morphology and biochemical characteristics, then confirmed using 16S rRNA gene-specific for the genus Vibrio and multiplex PCR using species-specific primers. 52 (34. 6%) Vibrio isolates were obtained from examined fishes. The highest incidence of Vibrio species was detected in C. gariepinus (64%), followed by M. cephalus (36%) and then O. niloticus (24%). In the case of C. gariepinus, V. alginolyticus was the most predominant species (32%), followed by V. fluvialis (12%), V. cholerae, V. parahaemolyticus (8%), and V. splendidus (4%). In the case of O. niloticus, the predominant Vibrio species were V. alginolyticus (12%), followed by V. parahaemolyticus (5. 33%), V. cholerae (4%), and then V. splendidus and anguillarum (1. 33%). In M. cephalus, V. alginolyticus also wasthe predominant species (14%), followed by V. cholerae (12%), V. parahaemolyticus, V. fluvialis (2%), and V. splendidus (2 %). V. alginolyticus, V. cholerae, and V. parahaemolyticus were found to produce PCR products of 737, 304, and 897 bp, respectively. This study highlights the incidence of Vibrio species in fish in Egypt.